Physical Activity, Exercise Motivations, Depression, and Nonsuicidal Self‐Injury in Youth. Issue 5 (11th March 2016) - Boone, Shannon D.; Brausch, Amy M.
Abstract : This study explored the relationship between physical activity, depression, and nonsuicidal self‐injury (NSSI) in 167 high school and undergraduate students (mean age = 17.37, range 14–25). Results indicated that NSSI frequency had a significant negative relationship with physical activity, and physical activity moderated the relationship between depressive symptoms and self‐harm. Specifically, high levels of depressive symptoms and low levels of physical activity had the greatest frequency of NSSI. Lastly, appearance‐based exercise motivations were significantly related to increased frequencies of NSSI. Overall, physical activity may possess a protective nature against NSSI, especially in individuals with depressive symptoms.